A Comparative Study to Assess the Fetal Outcome Among Normal and Anemic Mothers at Sultania Zanana Hospital at Bhopal - Kalpana Yadav (International Journal of Midwifery Nursing And Practices, 2025)
Anemia during pregnancy is a significant public health concern, especially in developing countries like India. It is a clinical condition characterized by a deficiency in hemoglobin levels, often due to inadequate intake of essential nutrients such as iron, folic acid, and vitamins. The World Health Organization classifies anemia during pregnancy as having hemoglobin levels under 11 g/dL, with specific thresholds varying by trimester. Maternal anemia not only affects the mother's health but also has profound implications on fetal outcomes, including intrauterine growth restriction (IUGR), low birth weight, preterm birth, and increased perinatal morbidity and mortality. This comparative study aims to assess and compare fetal outcomes among normal (non-anemic) and anemic mothers admitted to Sultania Zanana Hospital in Bhopal. It explores the extent to which anemia impacts placental function and fetal development. Factors contributing to maternal anemia, such as poor dietary habits, low socioeconomic status, early or late maternal age, and comorbid conditions, are considered. The study underscores the critical role of early identification, dietary adjustments, iron intake, and prenatal care in reducing the risk of complications. This research is expected to support the development of public health initiatives and contribute to better health outcomes for mothers and their unborn children. By highlighting the critical relationship between maternal anemia and neonatal health, the study underlines the need for coordinated efforts involving healthcare professionals, policymakers, and community organizations to mitigate anemia’s impact and promote healthier pregnancies and births.
Keywords: Maternal anemia; fetal outcomes; hemoglobin levels; pregnancy complications; prenatal care